Clinical and radiographic changes around dental implants inserted in different levels in relation to the crestal bone, under different restoration protocols, in the dog model - Pontes, Ana Emilia F.; Ribeiro, Fernando S.; da Silva, Vanessa C. [UNESP]; Margonar, Rogerio; Piattelli, Adriano; Cirelli, Joni Augusto [UNESP]; Marcantonio, Ecio [UNESP] (Amer Acad Periodontology, 2008)
Background: The aim of the present study was to evaluate clinical and radiographic changes that occur around dental implants inserted in different levels in relation to crestal bone under different restoration protocols.Methods: Thirty-six implants were inserted in the edentulous mandible of six mongrel dogs. Each implant was assigned to an experimental group according to the distance from the top of the implant to the crestal bone: Bone Level (at crestal bone level), Minus 1 (1 mm below crestal bone), or Minus 2 (2 mm below crestal bone). Each hemimandible was submitted to a restoration protocol: conventional (prosthesis was installed 120 days after implant placement, including 30 days with healing cap) or immediate (prosthesis was installed 24 hours after implant placement). Fixed partial prostheses were installed bilaterally in the same day. After 90 days, clinical and radiographic parameters were evaluated.Results: As long as the implants were inserted in more apical positions, the first bone-to-implant contact (fBIC) was positioned more apically (P<0.05). However, the apical positioning of the implants did not influence the ridge loss or the position of the soft tissue margin (PSTM) (P>0.05). In addition, in immediately restored sites, the PSTM was located significantly more coronally than that in conventionally restored sites (P=0.02).Conclusions: Despite the more apical positioning of the fBIC, the height of the peri-implant soft tissues and ridge was not jeopardized. Moreover, the immediate restoration protocol was beneficial to the maintenance of the PSTM. Further studies are suggested to evaluate the significance of these results in longer healing periods.
Keywords: animal studies; dental implants; esthetics; models; animal; prosthesis; radiography